Probing the Pomeron spin structure with Coulomb-nuclear interference - Kopeliovich, Boris Z.; Krelina, Michal; Potashnikova, Irina K. (Physics letters, 2021)
Polarized pp elastic scattering at small angles in the Coulomb-nuclear interference (CNI) region offers a unique opportunity to study the spin structure of the Pomeron. Electromagnetic effects in elastic amplitude can be equivalently treated either as Coulomb corrections to the hadronic amplitude (Coulomb phase), or as absorption corrections to the Coulomb scattering amplitude. We perform the first calculation of the Coulomb phase for the spin-flip amplitude and found it significantly exceeding the widely used non-flip Coulomb phase. The alternative description in terms of absorption corrections, though equivalent, turned out to be a more adequate approach for the Coulomb corrected spin-flip amplitude. Inspired by the recent high statistics measurements of single-spin asymmetry with the HJET polarimeter at the BNL, we also performed a Regge analysis of data, aiming at disentangling the Pomeron contribution. However, in spite of an exceptional accuracy of the data, they do not allow to single out the Pomeron term, which strongly correlates with the major sub-leading Reggeons. A stable solution can be accessed only by making additional ad hoc assumptions, e.g. assuming the Pomeron to be a simple Regge pole, or fixing some unknown parameters. Otherwise, in addition to the STAR data at s=200GeV new measurements, say at 100GeV or 500GeV, could become decisive.
Gesehen am 21.06.2021